Vector-Borne Dynamics of Canine Babesia Species: A Study on Trans-Stadial and Trans-Ovarian Transmission - Ramalingam, Vijayashanthi (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Canine babesiosis is an emerging haemoprotozoan disease affecting domestic and wild canids, globally. Among the primary vectors, Rhipicephalus sanguineus and Haemaphysalis longicornis play crucial roles in the disease transmission dynamics. The present study was aimed to investigate the potential role of different life stages of R. sanguineus in the transmission of canine babesiosis. Genomic DNA was extracted from various life stages of R. sanguineus ticks. 18S rRNA based molecular analysis revealed that 7.0% (23/330) of the samples were positive for Babesia species. Semi-nested PCR analysis showed no amplification for any Babesia species in DNA extracted from male ticks. A single DNA sample from a pool of eggs laid by an infected female tick tested positive for Babesia gibsoni, although further molecular and sequencing analyses are required for confirmation. This vector-based molecular epidemiological study indicated that R. sanguineus is more commonly associated with the transmission of Babesia vogeli (74.01%) than Babesia gibsoni (25.95%).